Virtual Reality for Introducing Informatics Laboratory on University of Trunojoyo Madura - muzamil muzamil; Cucun Very Angkoso; ari kusumaningsih (Universitas Trunojoyo Madura, 2016)
Nowadays, the development of increasingly advanced technology, one of the rapidly evolving technology at this time that smartphones based on Android. However, the development of technology is not comparable with the needs of students, for example in the introduction of the laboratory environment. During the introduction of the lab environment is still done manually without involving a technology to introduce a laboratory environment and it is less effective and efficient because need effort and a long time. For of these problem is make a Virtual Reality(VR) based android of 3D architectural visualization with a study area of information Technology Laboratory (TIF) UTM. From this application, students can explore and get to know Laboratories TIF simply using a smartphone based on Android, so students do not need to come lively. From the test result data, laboratory TIF VR applications can run well in 6 test device but the device Andromax R1 gyroscope is not functioning properly. From the results of testing applications using a questionnaire obtained, the average value of the respondents based user verification is 89% good, 11% Less good, and 0% unfavorable. And the average value of the entire question by 95%.